Performance analysis of 8kbps voice codec (G.729, G.711 ALAW, G.711 ULAW) for voip over wireless local area network with respective signal-to-noise ratio NOISE RATIO - Norani, Mohammad Zaki (2013)
In this research, 3 types of speech codec (G.729, G.711 aLaw and G.711 uLaw) in the same sampling rate of 8kbps are put to test in predefined network environment and given respective SNR 10dB, 20dB and 30dB to measure the performance base on R-factor, MOS, packet jitter and packet lost. Speech codec is used to convert the analog voice signals into digital signal. Each speech codec have its own speech quality, minimum bandwidth require etc. There are many manufacturers that have been producing various types of speech codecs in the market. The VoIP users are able to choose the desire codec that will be used or enable in the VoIP call based on the service and hardware that can support the speech codec. But, users will face some difficulty in choosing the best codec to use. All 3 mentioned speech codec will be test base on these criteria; VoIP session over optimum wireless network with 10dB, 20dB and 30dB SNR and VoIP session over wireless network that shared with other traffic with 10dB, 20dB and 30dB SNR. Six testbed will be carry out to complete all the criteria and all of the tests criteria will be carry out on real devices simulation. At the end, the performance measurement such as MOS, r-factor , packet lost and packet jitter will be observe to determine the best speech codec in each scenario. The final results of this research should be able to determine the best speech codec among the four codecs that have been selected and match the suitability with the environments.